2023
DOI: 10.1038/s42003-023-04545-3
|View full text |Cite
|
Sign up to set email alerts
|

Time-varying SUVr reflects the dynamics of dopamine increases during methylphenidate challenges in humans

Abstract: Dopamine facilitates cognition and is implicated in reward processing. Methylphenidate, a dopamine transporter blocker widely used to treat attention-deficit/hyperactivity disorder, can have rewarding and addictive effects if injected. Since methylphenidate’s brain uptake is much faster after intravenous than oral intake, we hypothesize that the speed of dopamine increases in the striatum in addition to its amplitude underly drug reward. To test this we use simulations and PET data of [11C]raclopride’s binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 63 publications
1
4
0
Order By: Relevance
“…Fourth, oral and IV drug administrations may vary on other unmeasured factors aside from the speed of dopamine increases, such as differences in MP metabolism when administered orally versus IV. However, in a prior analysis of this dataset [ 6 ] we confirmed that the oral and IV MP doses elicited similar overall striatal dopamine increases supporting the interpretation that the differences we observed are driven by the rate of dopamine change. Still, IV MP likely elicits a greater peak dopamine increase than oral MP, which we hypothesize could also contribute to greater D1R stimulation and unique connectivity patterns.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Fourth, oral and IV drug administrations may vary on other unmeasured factors aside from the speed of dopamine increases, such as differences in MP metabolism when administered orally versus IV. However, in a prior analysis of this dataset [ 6 ] we confirmed that the oral and IV MP doses elicited similar overall striatal dopamine increases supporting the interpretation that the differences we observed are driven by the rate of dopamine change. Still, IV MP likely elicits a greater peak dopamine increase than oral MP, which we hypothesize could also contribute to greater D1R stimulation and unique connectivity patterns.…”
Section: Discussionsupporting
confidence: 85%
“…Here, we replicated some of these results and found that connectivity patterns are crucially related to the dynamics of dopamine increases. The oral and IV doses in this study (60 mg and 0.25 mg/kg, respectively) occupy roughly equivalent quantities of striatal dopamine transporters (~70%) in humans [ 52 , 53 ], and produce roughly the same overall magnitude of dopamine increases [ 6 ]. Yet the connectivity patterns to slow and fast dopamine increases were opposing in most networks, and no regions showed significant overlap in connectivity patterns.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations